Electrical activity of the cerebral cortex in men having high or low output alpha-frequencies while performing usual manual movements in response to sensory signals - Morenko, Alevtyna H.; Tsos, Anatolii V.; Kotsan, Ihor Ya.; Моренко, Алевтина Григорівна; Цьось, Анатолій Васильович; Коцан, Ігор Ярославович (Państwowa Szkoła Wyższa im. Papieża Jana Pawła II w Białej Podlaskiej, 2013)
A test group consisting of 104 healthy men from the ages of 19 to 21 was divided into two groups according to the magnitude of their individual α- frequency (ІАF) median―groups with high (n = 53, IA ≥ 10,04 Hz) and low (n = 51, IAF ≤ 10,03 Hz) levels of ІАF. Changes in power and coherence of the EEG oscillations during the usual manual movements as well as intergroup differences were evaluated. The higher level of the background tone of the cortex activation in men with a high IAF (individual alpha-frequency) was found as correlative with a significant selection of the relevant sensory information and a nonspecific input afferentation and its weakening under the performance of habitual manual movements. A functional state of the cortex is relatively lower in men with a low IAF and compensated by the tension of brain processes associated with a low level of the selective attention and the increase of the reticular influences and their significance during the finger movements. Men with a high IAF are characterized by the greater locality and asymmetry of processes of the cortical excitation under the dominant role of the left hemisphere. Activation changes are more diffuse in nature in subjects having a low frequency.
Keywords: electroencephalogram; individual alpha-frequency; usual manual motion